Towards a Theory of Software Developer Job Satisfaction and Perceived Productivity - Storey, Margaret-Anne; Zimmermann, Tom; Bird, Christian; Czerwonka, Jacek; Murphy, Brendan; Kalliamvakou, Eirini (IEEE Transactions on Software Engineering, 2019)
Developer satisfaction and work productivity are important considerations for software companies. Enhanced developer satisfaction may improve the attraction, retention and health of employees, while higher productivity should reduce costs and increase customer satisfaction through faster software improvements. Many researchers and companies assume that perceived productivity and job satisfaction are related and may be used as proxies for one another, but these claims are a current topic of debate. There are also many social and technical factors that may impact satisfaction and productivity, but which factors have the most impact is not clear, especially for specific development contexts. Through our research, we developed a theory articulating a bidirectional relationship between software developer job satisfaction and perceived productivity, and identified what additional social and technical factors, challenges and work context variables influence this relationship. The constructs and relationships in our theory were derived in part from related literature in software engineering and knowledge work, and we validated and extended these concepts through a rigorously designed survey instrument. We instantiate our theory with a large software company, which suggests a number of propositions about the relative impact of various factors and challenges on developer satisfaction and perceived productivity. Our survey instrument and analysis approach can be applied to other development settings, while our findings lead to concrete recommendations for practitioners and researchers.